Pemetaan Penderita Pneumonia Terhadap Kondisi Lingkungan Di Jakarta - Nityasa Tustika; Bambang Agus Herlambang; Ahmad Khoirul Anam (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Pneumonia is a serious problem in dense urban areas, especially in Jakarta. This article discusses the mapping of pneumonia sufferers and their relationship with environmental factors in Jakarta. Non-spatial data involves information about pneumonia sufferers, Air Quality Index (IKU), Water Quality Index (IKA), Land Cover Quality Index (IKTL), and the number of macro industries. It is hoped that the mapping results will provide in-depth insight into disease distribution patterns and environmental factors that have the potential to influence the spread of pneumonia. By understanding the environmental factors that play a role, it is hoped that it can help develop effective prevention strategies to deal with the spread of pneumonia.